2020
DOI: 10.31729/jnma.5149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Anomalies in the Patient with Cleft Lip and Palate Visiting a Tertiary Care Hospital

Abstract: Introduction: Dental anomaly is one of the major problems in a child born with cleft lip and palate. These anomalies have deleterious effects on the dentition leading to aesthetic problems, impairment of mastication andimproper phonation. The aim of our study was to find out the prevalence of dental anomalies in patient with cleft lip and/or palate radiographically. Methods: A descriptive cross-sectional study was conducted from the 208 radiographs, collected by the convenience samplingtechnique with cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 13 publications
5
16
1
4
Order By: Relevance
“…Tereza et al (2010) in a group of 205 patients with cleft lip and palate found a frequency of supernumerary teeth of 11.7%. Pradhan et al (2020) in the Iranian population of children with cleft revealed 15% prevalence. The Polish sample examined presented a 26.55% occurrence, which is a much higher result.…”
Section: Discussionmentioning
confidence: 96%
“…Tereza et al (2010) in a group of 205 patients with cleft lip and palate found a frequency of supernumerary teeth of 11.7%. Pradhan et al (2020) in the Iranian population of children with cleft revealed 15% prevalence. The Polish sample examined presented a 26.55% occurrence, which is a much higher result.…”
Section: Discussionmentioning
confidence: 96%
“…Outside the cleft area, the most affected teeth are the lateral incisor contralateral to the cleft and the second premolars (Ajami et al, 2017;Huda et al, 2021;Konstantonis et al, 2017;Pradhan et al, 2020).…”
Section: Final Cons Ider Ationsmentioning
confidence: 99%
“…Subjects with NSOC are often affected by developmental anomalies associated with the primary and secondary dentitions (Cakan et al, 2018); however, studies show a higher prevalence in the permanent dentition with variations in percentages, demonstrating significant heterogeneity among the epidemiological studies that have evaluated dental anomalies in patients with NSOC (Yow et al, 2020; Nzomiwu et al, 2021; Pradhan et al, 2020; Mangione et al, 2018; Ajami et al, 2017; Nicholls, 2016; Nicholls et al, 2016; Akcam et al, 2010; Stahl et al, 2006; Wangsrimongkol et al, 2013).…”
Section: Final Considerationsmentioning
confidence: 99%
See 2 more Smart Citations